Enrichment of prevotella melaninogenica in the lower respiratory tract links to checkpoint inhibitor pneumonitis and radiation pneumonitis - Chen, Jiajun; Xu, Qiong; Zhang, Liyan; Zhang, Donglei; Wu, Xueling (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundCheckpoint inhibitor pneumonitis (CIP) and radiation pneumonitis (RP) lead to anti-cancer therapy discontinuation and poor diagnosis. The human microbiome is related to various respiratory diseases. However, the role of the lung microbiome in CIP and RP remains unknown. Our study aimed to explore the lower respiratory tract (LRT) microbiome in CIP/RP patients.MethodsThe study enrolled 61 patients with pneumonitis or pneumonia, including 23 with CIP/RP, and 38 with lung cancer with pneumonia (LC-P). Metagenomic next-generation sequencing (mNGS) was performed to identify the microbiota in bronchoalveolar lavage fluid (BALF), and bioinformatics methods were used to compare the microbial differences between CIP/RP and LC-P groups. Correlation analysis was conducted to explore the relationship between LRT microbiota and clinical features.ResultsThe Prevotella was the dominant genus in both groups. The Prevotella melaninogenica, which belongs to the Prevotella genus, was the dominant species in the CIP/RP group and the second most abundant species in the LC-P group. Compared to the LC-P group, the CIP/RP group had significantly high levels of Prevotella melaninogenica species and lymphocyte percentage in BALF but significantly low levels of lymphocytes, eosinophils and albumin in peripheral blood. In addition, the Prevotella melaninogenica species had a negative correlation with peripheral blood lymphocytes.ConclusionThe enrichment of Prevotella melaninogenica species in LRT and a decreased level of peripheral blood lymphocytes are associated with CIP/RP.